Structural Differences Between Spoken and Written English Syntax (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper examines the structural syntactic differences between spoken and written English using descriptive, comparative, and corpus-informed approaches. Spoken English, shaped by spontaneity and interaction, tends toward parataxis, ellipsis, and discourse markers. Written English, influenced by planning and editing, prefers hypotaxis, nominalization, and greater lexical density. The study presents an IMRAD-structured analysis highlighting cognitive, social, and communicative factors influencing the syntactic divergence between the two modes.